Reading Development among Swedish Children: The Importance of Contextual Resources and Language Ability - Birgitta Herkner (Taylor & Francis Group, 2021)
Language abilities in preschool years, including those measured with letter knowledge, are predictors of reading development in later school years. The aim of this study was to investigate variation in children’s language abilities before they started school in relation to gender and neighborhood level socioeconomic status (SES). Schools from three municipalities with varied resources and living conditions participated in this study. The participants were 231 children 4–6 years old (girls n = 117, boys n = 114; mean age 4.8 years old; SD = 6 months). In this cross-sectional study, children took the Rapid Automatized Naming (RAN) object test and a Letter Knowledge task. Results showed no significant differences in task performance between boys and girls. Children attending preschools situated in average to above average SES areas had higher scores on the RAN object task compared to those who attended preschools located in low SES neighborhoods. Finally, a significant association was found between children’s first language and SES. The implications of these results are explored in this article.